2020
DOI: 10.21203/rs.2.23662/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IL-37 Gene Modification Enhances the Protective Effects of Mesenchymal Stromal Cells on Intestinal Ischemia Reperfusion Injury

Abstract: Background: Ischemia reperfusion injury (IRI) is the major cause of intestinal damage in clinic. Although either mesenchymal stromal cells (MSCs) or interleukin 37 (IL-37) showed some beneficial roles to ameliorate IRI, their effects are limited. In this study, the protective effects of IL-37 gene-modified MSCs (IL-37-MSCs) for better prevention of intestinal IRI are investigated.Methods: Intestinal IRI model was established by occluding the superior mesenteric artery for 30min and then reperfusing for 72 hour… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…IL-37 gene-modified MSCs (IL-37-MSCs) can distinctly inhibit intestinal ischemia reperfusion injury (IRI) by migrating to the damaged tissue (47). Indeed, the treatment with IL-37-MSCs on IRI rats strengthens gut barrier function and reduced the local and systemic level of the inflammatory cytokine IL-1b, as compared with rats treated with MSCs or recombinant IL-37 (47).…”
Section: Effects On Mesenchymal Stem Cells By Il-37mentioning
confidence: 99%
See 1 more Smart Citation
“…IL-37 gene-modified MSCs (IL-37-MSCs) can distinctly inhibit intestinal ischemia reperfusion injury (IRI) by migrating to the damaged tissue (47). Indeed, the treatment with IL-37-MSCs on IRI rats strengthens gut barrier function and reduced the local and systemic level of the inflammatory cytokine IL-1b, as compared with rats treated with MSCs or recombinant IL-37 (47).…”
Section: Effects On Mesenchymal Stem Cells By Il-37mentioning
confidence: 99%
“…IL-37 gene-modified MSCs (IL-37-MSCs) can distinctly inhibit intestinal ischemia reperfusion injury (IRI) by migrating to the damaged tissue (47). Indeed, the treatment with IL-37-MSCs on IRI rats strengthens gut barrier function and reduced the local and systemic level of the inflammatory cytokine IL-1b, as compared with rats treated with MSCs or recombinant IL-37 (47). In addition, IL-37-MSCs treatment in IRI rats significantly decreases tissue damage due to NLRP3, the downstream targets such as cleaved caspase-1, IL-1b, and IL-18, and IL-1b-and IL-18-related proinflammatory mediators IL-6 and TNF-a mRNA expression, suggesting that NLRP3-related signaling pathway could be associated to the protection mediated by IL-37-MSC (47).…”
Section: Effects On Mesenchymal Stem Cells By Il-37mentioning
confidence: 99%
“…After title and abstract screening, 25 articles were identified and underwent review of the full text. Ultimately, 7 studies were included in the meta-analysis [4,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] (Fig. 1).…”
Section: Study Screenmentioning
confidence: 99%
“…MSCs release many types of cytokines factors through paracrine effects or directly interacts with immune cells, leading to immunomodulation. The included studies showed that MSCs positively contributed to recovery process by decreasing pro-inflammatory cytokines (TNF-α, IL-6, IL-1β, TGF-β1, MPO, NF-κB, and iNOS) [4,18,21,23,26,27,29] and increasing anti-inflammatory cytokines (EP3 and IL-1Ra) [18] following IRI in the intestine of animals. The Toll/Interleukin-1 receptor (TIR) domain is highly conserved among all toll-like receptors (TLRs) and triggers the TLR-mediated signaling pathways.…”
Section: Protective Effect Of Mscs Related To Inflammationmentioning
confidence: 99%
“…It has been demonstrated that the transgenic mice expressing human IL-37 gene can protect them from different pro-inflammatory situations, such as ulcerative colitis (UC) [40] and LPS-induced endotoxemia [38]. Moreover, we and others have reported that IL-37 has synergistic effects with MSCs or ERCs in attenuation of UC [41], intestinal ischemia-reperfusion injury [42], concanavalin A-induced hepatitis [43], and SLE [44] via different mechanisms. Recently, our ongoing study has also demonstrated the effects of recombinant IL-37 in inhibition of acute cardiac allograft rejection.…”
Section: Introductionmentioning
confidence: 99%